Preparation method of high-purity oxygen-free copper cast ingot and radio frequency assembly
Through step-up heating and preheating and covering with scale graphite or nano-carbon tubes, combined with argon stirring and multi-stage overflow separation, the problem of low oxygen content of high-purity oxygen-free copper ingots is solved, and the high purity and uniformity of copper ingots is achieved, which significantly improves the performance and service life of radio frequency components.
Patent Information
- Application Number
- CN202411900869.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The domestic high-purity oxygen-free copper ingot has low oxygen content and cannot meet the 4N or 5N standards, resulting in unstable product quality and poor consistency, affecting the performance and service life of RF components.
The step-up heating of the electrolytic copper plate is used to preheat the electrolytic copper plate, covered with scale graphite or nanocarbon tubes, and is smelted and purified, combined with argon stirring and multi-stage overflow separation to ensure the high purity and uniformity of the copper liquid.
It significantly improves the electrical, thermal and mechanical properties of copper ingots, reduces the risk of hydrogen embrittlement and other defects, and ensures that the internal structure of the copper ingots is uniform and dense, suitable for the manufacturing of high-performance radio frequency components.
Smart Images

Figure CN119710321A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of metal ingot manufacturing, and specifically relates to a preparation method of a high-purity oxygen-free copper ingot and a radio frequency component. Background Art
[0002] Oxygen-free copper has high electrical and thermal conductivity, good weldability, excellent plasticity and ductility, excellent cold processing performance and is non-magnetic. It is widely used in the electronics industry, especially in vacuum electronic devices. In recent years, in the field of precision electronics, oxygen-free copper is required to reach 4N (99.99%) and 5N (99.999%). Domestic oxygen-free copper usually has a copper content of 99.95-99.98%, which cannot meet the standard of high-purity oxygen-free copper (TU00), and the oxygen content is usually controlled at more than 5ppm. When processing equipment (such as communication equipment such as radio frequency components or optical fiber connectors and semiconductor equipment such as PCB boards), hydrogen embrittlement is easy to occur, thereby affecting the service life of the equipment and the consistency of the performance of the processed parts.
[0003] At present, the domestic high-purity oxygen-free copper has high production costs, and the product quality is unstable and the consistency is poor. Therefore, the country urgently needs to stably produce high-purity oxygen-free copper with copper content of 4N and 5N, low impurity content and low oxygen content to solve the problem of high-quality high-purity oxygen-free copper relying on imports. Summary of the invention
[0004] The main purpose of the present application is to provide a method for preparing a high-purity oxygen-free copper ingot and a radio frequency component. The present application aims to solve the problem that the existing oxygen-free copper ingot has low oxygen content and cannot meet the standard.
[0005] To achieve the above objectives, this application provides the following technical solutions:
[0006] A method for preparing a high-purity oxygen-free copper ingot, the method comprising: preheating and drying an electrolytic copper plate; smelting the dried electrolytic copper plate to obtain copper liquid; keeping the copper liquid warm and stirring it during the keeping warm process to purify the copper liquid; initially cooling the purified copper liquid to obtain a copper ingot; drawing the copper ingot, secondary cooling the copper ingot during the drawing process, and sawing and casting the secondary cooled copper ingot to obtain a high-purity oxygen-free copper ingot.
[0007] Optionally, the electrolytic copper plate is preheated in a step-by-step heating manner, with the preheating temperature being 300°C to 500°C.
[0008] Optionally, the smelting temperature of the electrolytic copper plate is 1200°C to 1300°C.
[0009] Optionally, after obtaining the molten copper, it is necessary to cover the surface of the molten copper with flake graphite, and the thickness of the flake graphite is 50 mm to 100 mm.
[0010] Optionally, the insulation time of the copper liquid is 1 h to 4 h.
[0011] Optionally, cooling water is used to perform primary cooling and secondary cooling on the purified copper liquid. The flow rate of cooling water for primary cooling is set to 40m 3 / h~50m 3 / h.
[0012] Optionally, the cooling water adopts a flow path from top to bottom.
[0013] Optionally, during the secondary cooling of the copper ingot, the spray intensity of the cooling water is set in a gradient manner.
[0014] Optionally, before sawing and casting the copper ingot after secondary cooling, the copper ingot needs to be cold treated.
[0015] The present application also provides a radio frequency component, wherein the radio frequency component is made of high-purity oxygen-free copper, and the high-purity oxygen-free copper is prepared by any of the preparation methods described above.
[0016] This application can bring the following beneficial effects:
[0017] This solution can produce high-purity copper materials with a copper content of more than 99.99% and extremely low impurity content, significantly improving the electrical conductivity, thermal conductivity and mechanical properties of copper ingots, and effectively reducing the risk of hydrogen embrittlement and other defects. This application can ensure that the internal structure of copper ingots is uniform and dense, with excellent surface quality, suitable for manufacturing high-performance RF components (such as antennas, filters and couplers), greatly improving the reliability and service life of products, while optimizing processing performance and electromagnetic compatibility, and meeting the strict requirements of high-end manufacturing for high-quality materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic flow chart of a method for preparing a high-purity oxygen-free copper ingot provided in one embodiment of the present application;
[0019] Figure 2 This is a macroscopic metallographic diagram of an oxygen-free copper ingot prepared by the method described in the present application;
[0020] Figure 3 This is a microscopic metallographic image of an oxygen-free copper ingot prepared by the method described in the present application;
[0021] Figure 4 This is a macroscopic metallographic diagram of the existing oxygen-free copper ingot. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0023] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0024] In this application, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0025] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0026] Figure 1 FIG. 1 is a schematic flow diagram of a method for preparing a high-purity oxygen-free copper ingot according to an embodiment of the present application, such as Figure 1 As shown, the preparation method comprises:
[0027] S1: preheating the electrolytic copper plate and then drying it, wherein the preheating adopts a step-by-step heating method, that is, starting from room temperature, the temperature is increased by 25°C per hour until the temperature reaches 300°C, and the temperature is kept at 300°C for 1 hour;
[0028] In this step, it has been found through experiments that the electrolytic copper plate can be heated quickly from room temperature to high temperature, which will cause a sharp temperature gradient inside the plate, thereby inducing thermal stress. This thermal stress can cause the electrolytic copper plate to deform, crack, or even break. By increasing the temperature in a stepwise manner, the heat can be evenly distributed throughout the electrolytic copper plate over a sufficient period of time, reducing the thermal stress caused by the temperature difference, thereby protecting the integrity of the overall structure of the electrolytic copper plate. In addition, many impurities (such as oxides, sulfides, etc.) attached to the electrolytic copper plate require a certain amount of time and temperature conditions to decompose or volatilize. For example, copper oxide (CuO) and cuprous oxide (Cu 2 O) begins to decompose into metallic copper and oxygen at lower temperatures; copper sulfate (CuSO 4 ) will gradually decompose within a certain temperature range and release sulfur dioxide (SO 2 ) and water vapor (H 2 O). The heating rate of 25°C / hour provides sufficient residence time so that these chemical reactions can fully proceed in each temperature range, ensuring that impurities are effectively removed.
[0029] In summary, by adopting a step-by-step preheating process and setting various preheating parameters, the copper oxide, cuprous oxide, copper sulfate and other substances attached to the surface of the electrolytic copper plate can be decomposed and eliminated to reduce the impact of these impurities on the purity of the copper liquid in the subsequent smelting process. After preheating, drying treatment is then carried out to further remove moisture or other volatile substances that may exist on the surface of the electrolytic copper plate, ensuring that the material entering the smelting process is as pure as possible and avoiding the introduction of unnecessary impurities or gases during the melting process.
[0030] S2: Put the dried electrolytic copper plate into a graphite crucible in a vertical continuous casting furnace at a temperature of 1200°C to melt to obtain molten copper. At the same time, the surface of the molten copper is covered with flake graphite with a thickness of 50 mm to 100 mm, and the molten copper is introduced into a homogenization chamber from an overflow hole at the bottom of the graphite crucible;
[0031] In this step, the graphite crucible is made of high-purity graphite, which can prevent the introduction of new impurities during the smelting process. In addition, the use of flaky graphite to cover the surface of the molten copper can not only prevent oxygen in the air from contacting the molten copper, but also help maintain the purity of the molten copper. In addition, a partition is provided in the graphite crucible, and when the molten copper flows from the graphite crucible into the homogenization chamber, the partition can effectively block and separate oxides and other impurities in the molten copper, thereby achieving preliminary purification of the molten copper.
[0032] In addition, in addition to limiting the thickness of flake graphite, the present application further innovatively designs the distribution mode and coverage concentration of flake graphite. For the distribution mode, the present application adopts a combination of spray deposition and layered accumulation. Spray deposition is to use airflow or liquid carrier to spray graphite particles evenly onto the surface of copper liquid to ensure that each area is fully covered; layered accumulation is to guide graphite particles to be arranged in layers by a specific mold or template to form an orderly covering structure, which not only improves the coverage efficiency of flake graphite, but also enhances its impact resistance. The present application combines spray deposition (ensuring uniform distribution) with layered accumulation (building an ordered structure), not only considering the uniformity and density of the flake graphite covering layer, but also enabling flake graphite to form a more stable and effective protective layer, which can more effectively reduce the chance of copper liquid contacting with air than simply setting the covering thickness. In addition, taking into account the environmental differences that different parts of the copper ingot may face (such as the edge and the center), the present application uses flake graphite with different concentration gradients to cover the molten copper. For example, the amount of flake graphite is increased in the key area of the copper liquid surface near the edge of the ingot to strengthen the edge protection, thereby further improving the mechanical properties and durability of the copper ingot, while maintaining a lower concentration in the central part of the copper liquid surface to facilitate gas discharge and reduce the possibility of internal defects in the copper ingot, thereby improving the purity and uniformity of the copper ingot finally prepared.
[0033] Through the above-mentioned design, the present application not only enhances the protective effect of the flake graphite covering layer on the copper liquid in key areas, but also optimizes the functional zoning of the entire flake graphite covering layer, ensuring the high-quality formation of the copper liquid during the entire cooling and solidification process.
[0034] S3: The copper liquid is kept warm in the homogenization chamber for 1 hour. At the same time, argon gas is continuously blown into the copper liquid (the argon gas flow rate is controlled at 25L / min to 45L / min) to stir the copper liquid. After the stirring is completed, the copper liquid is introduced into the alloying crucible through the drainage tube for further purification.
[0035] In this step, by heat preservation, the composition inside the copper liquid can be made more uniform, even if a higher temperature has been reached during the smelting process, some trace impurities or alloy elements will not be immediately evenly distributed in the entire copper liquid, and by heat preservation, these components are fully diffused to avoid local enrichment. In addition, by heat preservation, the copper liquid can reach temperature equilibrium in the entire volume, eliminating the local overheating or supercooling problem caused by the temperature difference of different parts during the smelting process, thereby preventing the generation of cracks and other defects.
[0036] During the insulation process, the copper liquid can be effectively stirred by continuously introducing argon gas, making the internal composition of the copper liquid more uniform. More importantly, as an inert gas, argon gas can cause the residual impurities in the copper liquid to float to the surface without introducing new impurities, thereby achieving further purification.
[0037] In addition, the alloying crucible is designed as three independent chambers, each of which is provided with an overflow port. When the copper liquid overflows from one chamber to the next, each overflow is accompanied by the separation of impurities. Due to the effect of the graphite partition and the stratification effect naturally formed by the copper liquid itself during the flow process, the heavier impurities are deposited below, while the pure copper liquid flows upward smoothly. Through this multi-stage overflow method, the copper liquid is purified multiple times during the transfer process between different chambers, greatly reducing the content of residual impurities and ensuring that the final copper liquid has extremely high purity.
[0038] S4: The purified copper liquid flows from the alloying crucible into a launder heated to 1200°C, and then the copper liquid is introduced into a crystallizer through the launder. While the copper liquid flows in the launder, argon gas is continuously introduced to prevent oxidation of the copper liquid.
[0039] S5: After the copper liquid enters the crystallizer, cooling water is introduced into the crystallizer to form a cooling loop to perform primary cooling on the copper liquid, and a copper ingot is obtained after cooling and solidification. After the copper ingot is obtained, a billet drawing machine is started to pull the copper ingot downward at a speed of 30 mm / min to form a continuous copper ingot. When the copper ingot is pulled to a certain length, cooling water is continuously sprayed on the copper ingot for secondary cooling to obtain a completely solidified copper ingot.
[0040] In this step, during the initial cooling process, the cooling water flow rate is set to 40m 3 / h~50m 3 / h (The rapid cooling of the copper liquid is essential for the formation of a fine and uniform crystal structure. If the cooling rate is too slow, it may lead to coarse grains and affect the mechanical properties of the final product. By setting a higher cooling water flow rate (40m 3 / h~50m 3 / h), which can ensure that there is enough cooling capacity to quickly take away the heat, so as to achieve rapid cooling of the copper liquid), and the flow direction of the cooling water is water outflow from the top and water return from the bottom (wherein, "upper" refers to the position where the cooling water enters, that is, the cooling water is introduced from the top of the cooling system and flows to the surface of the copper ingot or the upper area of the crystallizer. "Downward" refers to the position where the cooling water flows out, that is, the cooling water is discharged from the system from the bottom after contacting the copper ingot or the wall of the crystallizer. Since the copper liquid solidifies from top to bottom, the use of a flow path from top to bottom can ensure that the cooling water first contacts the colder part that has been initially solidified, and then gradually advances to the area that has not yet been completely solidified, so as to avoid the situation where the bottom is cooled too quickly and the top is not cooled sufficiently, thereby achieving a more uniform overall cooling effect; in addition, when the cooling water flows from top to bottom, a continuous cooling film will be formed along the surface of the copper ingot. This cooling film can alleviate the thermal stress caused by the temperature difference to a certain extent, especially in places where the ingot wall thickness is uneven. Uniform cooling helps to reduce the accumulation of internal stress and prevent the occurrence of cracks and other defects). The primary cooling ensures that the surface of the copper liquid solidifies quickly to form a solid shell, thus providing the necessary structural support for subsequent billet drawing. In addition, during the process of the billet drawing machine pulling the copper ingot, since the copper liquid continuously flows from the alloying crucible into the crystallizer, it is necessary to keep the cooling water flowing so as to form a continuous copper ingot. In addition, the secondary cooling water is directly sprayed onto the surface of the copper ingot being formed to accelerate its cooling process, so that the internal temperature of the copper ingot drops rapidly and completes the final solidification and hardening.
[0041] It should be noted that for copper ingots of different lengths, the secondary cooling time should be different. For example, when the copper ingot is pulled to 2000mm and sawing begins, the secondary cooling can start from when the copper ingot reaches about 1800mm and continue until the sawing is completed. For longer copper ingots (such as 4000mm), the secondary cooling can be started when it is pulled to about 3500mm until the copper ingot is completely solidified and ready for sawing.
[0042] In addition, the cooling rate should be fast enough to ensure that the surface of the copper ingot hardens quickly, but not too fast to cause excessive internal stress or cracks. Typically, the secondary cooling time can be set to the time required from the start of cooling to the time when the surface temperature of the copper ingot drops to near ambient temperature. According to experience, this time range is generally between 5min and 15min, but it depends on the thickness and diameter of the copper ingot.
[0043] Furthermore, the present application has made a refined design of the injection intensity of the secondary cooling water, which specifically includes the following three stages:
[0044] Initial stage: At the beginning of secondary cooling, a lower spray intensity (e.g., water pressure 0.2MPa-0.4MPa) can be used, which helps to avoid thermal shock caused by sudden cooling and protect the newly formed surface of the copper ingot from damage. At this time, the water flow should form fine droplets that evenly cover the surface of the copper ingot.
[0045] Cooling period: As the cooling process progresses, the secondary cooling water injection intensity gradually increases to 0.6-0.8 MPa to accelerate heat conduction and rapidly reduce the internal temperature of the copper ingot. The water flow at this stage can be in the form of larger water drops or direct water flow to ensure sufficient cooling strength.
[0046] End stage: When the cooling is almost over, the spray intensity is reduced again to 0.2MPa-0.4MPa to reduce the internal stress generated in the final cooling stage. At the same time, this is also conducive to the drying of the copper ingot surface and facilitates subsequent processing.
[0047] In summary, secondary cooling can increase the cooling rate of the copper ingot, ensure that the inside and outside of the copper ingot can be cooled evenly and quickly, help reduce internal stress and defects, and thus improve the quality of the ingot.
[0048] S6: When the copper ingot is pulled to 2000mm, use a sawing machine to clamp the copper ingot and start sawing. The saw blade feed speed is 10mm / min. After the sawing is completed, the sawed copper ingot is turned out of the casting pit by a turning machine to obtain a high-purity oxygen-free copper ingot.
[0049] In another exemplary embodiment, the present application also provides a method for preparing a high-purity oxygen-free copper ingot, the preparation method comprising the following steps:
[0050] S10: preheating the electrolytic copper plate and then drying it, wherein the preheating adopts a step-by-step heating method, that is, starting from room temperature, the temperature is increased by 25°C per hour until the temperature reaches 400°C, and the temperature is kept at 400°C for 3 hours;
[0051] S20: putting the dried electrolytic copper plate into a graphite crucible in a vertical continuous casting furnace at a temperature of 1250° C. to melt to obtain molten copper, and at the same time, covering the surface of the molten copper with nano-carbon tubes with a thickness of 0.1 mm to 1 mm, and introducing the molten copper into a homogenization chamber from an overflow hole at the bottom of the graphite crucible;
[0052] In this step, compared with flake graphite, carbon nanotubes have better oxidation resistance and corrosion resistance. They can more effectively prevent the copper liquid from coming into contact with air and undergoing oxidation reaction under high temperature environment, and can better resist the erosion of the copper liquid by corrosive gas or corrosive liquid. In addition, flake graphite may release fine particles or dust during use. These impurities may mix into the copper liquid and affect the purity of the final product, while carbon nanotubes are less likely to do so, which helps maintain a higher purity of the copper liquid. In addition, when using flake graphite, operators may be exposed to graphite dust, which has a certain negative impact on health and the working environment. In contrast, the use of carbon nanotubes can significantly reduce such risks and help improve working conditions.
[0053] It should be noted that the thickness of the carbon nanotubes is set within the range of 0.1mm to 1mm, which has been verified to be reasonable. Within this thickness range, the carbon nanotubes can form a continuous and dense covering layer, effectively preventing the copper liquid from contacting the air and reducing the risk of oxidation. At the same time, it can also maintain structural integrity at high temperatures and provide lasting protection. Carbon nanotubes are a relatively expensive material. Too thick a covering layer will significantly increase the cost. 0.1mm to 1mm is an ideal range that can both meet functional requirements and control costs. If the covering thickness of the carbon nanotubes is less than 0.1mm, one is that the covering layer will not be dense enough, and there will be tiny gaps or holes, so that oxygen in the air can still penetrate into the surface of the copper liquid, affecting the antioxidant effect. Second, the thinner covering layer cannot provide sufficient mechanical strength to resist disturbances during the smelting process, such as the force generated during stirring, which may cause the covering layer to break or fall off. On the contrary, if the covering thickness of the carbon nanotubes is greater than 1mm, one is that the cost of use will increase, and the other is that the overly thick covering layer will affect the efficiency of heat conduction, resulting in a longer cooling time in the later stage, thereby reducing production efficiency.
[0054] S30: The copper liquid is kept warm in the homogenization chamber for 2 hours. At the same time, argon gas is continuously blown into the copper liquid (the argon gas flow rate is controlled at 25L / min to 45L / min) to stir the copper liquid. After the stirring is completed, the copper liquid is introduced into the alloying crucible through the drainage tube for further purification.
[0055] S40: The purified copper liquid flows from the alloying crucible into a launder heated to 1250° C., and then the copper liquid is introduced into a crystallizer through the launder. While the copper liquid flows in the launder, argon gas is continuously introduced to prevent oxidation of the copper liquid.
[0056] S50: After the copper liquid enters the crystallizer, cooling water is introduced into the crystallizer to form a cooling loop to perform primary cooling on the copper liquid, and a copper ingot is obtained after cooling and solidification. After the copper ingot is obtained, a billet drawing machine is started to pull the copper ingot downward at a speed of 40 mm / min to form a continuous copper ingot. When the copper ingot is pulled to a certain length, cooling water is continuously sprayed on the copper ingot for secondary cooling to obtain a completely solidified copper ingot.
[0057] S60: When the copper ingot is pulled to 3000mm, use a sawing machine to clamp the copper ingot and start sawing. The saw blade feed speed is 15mm / min. After the sawing is completed, the sawed copper ingot is turned out of the casting pit by a turning machine to obtain a high-purity oxygen-free copper ingot.
[0058] In another exemplary embodiment, the present application also provides a method for preparing a high-purity oxygen-free copper ingot, the preparation method comprising the following steps:
[0059] S100: preheating the electrolytic copper plate and then drying it, wherein the preheating adopts a step-by-step heating method, that is, starting from room temperature, the temperature is increased by 25°C per hour until the temperature reaches 500°C, and the temperature is kept at 500°C for 4 hours;
[0060] S200: putting the dried electrolytic copper plate into a graphite crucible in a vertical continuous casting furnace at a temperature of 1300° C. to melt to obtain molten copper, and at the same time, covering the surface of the molten copper with nano-carbon tubes with a thickness of 0.1 mm to 1 mm, and introducing the molten copper into a homogenization chamber from an overflow hole at the bottom of the graphite crucible;
[0061] S300: The copper liquid is kept warm in the homogenization chamber for 4 hours. At the same time, argon gas is continuously blown into the copper liquid (the argon gas flow rate is controlled at 25L / min to 45L / min) to stir the copper liquid. After the stirring is completed, the copper liquid is introduced into the alloying crucible through the drainage tube for further purification.
[0062] S400: The purified copper liquid flows from the alloying crucible into a launder heated to 1300°C, and then the copper liquid is introduced into a crystallizer through the launder. During the flow of the copper liquid in the launder, argon gas is continuously introduced to prevent oxidation of the copper liquid.
[0063] S500: After the copper liquid enters the crystallizer, cooling water is introduced into the crystallizer to form a cooling loop to perform primary cooling on the copper liquid, and a copper ingot is obtained after cooling and solidification. After the copper ingot is obtained, a billet drawing machine is started to pull the copper ingot downward at a speed of 50 mm / min to form a continuous copper ingot. When the copper ingot is pulled to a certain length, cooling water is continuously sprayed on the copper ingot for secondary cooling to obtain a completely solidified copper ingot.
[0064] S600: When the copper ingot is pulled to 4000mm, use a sawing machine to clamp the copper ingot and start sawing. The saw blade feed speed is 20mm / min. After the sawing is completed, the sawed copper ingot is turned out of the casting pit by a turning machine to obtain a high-purity oxygen-free copper ingot.
[0065] In the above embodiment, the preheating time of the electrolytic copper plate is set to 300℃~500℃, and the holding time is set to 2~4h. The reason is that: direct and rapid heating from room temperature to high temperature will cause a drastic temperature gradient inside the electrolytic copper plate, thereby inducing thermal stress, which will cause the electrolytic copper plate to deform, crack or even break. By stepwise heating to 300℃~500℃ and keeping warm for an appropriate time, the heat can be evenly distributed throughout the electrolytic copper plate, reducing the thermal stress caused by the temperature difference and protecting the overall structural integrity of the electrolytic copper plate. In addition, the holding time is set to 2h~4h to ensure that the above chemical reaction has enough time to fully proceed and to allow the electrolytic copper plate to reach temperature equilibrium. The insulation within this time range helps to ensure that all parts of the electrolytic copper plate can experience the same treatment effect.
[0066] In the above embodiment, the melting point of copper is about 1085°C. In order to ensure that the electrolytic copper plate can be completely melted, and considering the heat loss and temperature distribution unevenness in actual production, the smelting temperature needs to be set higher than the melting point of copper. The temperature range of 1200°C to 1300°C can ensure that the electrolytic copper plate is fully melted into a liquid state, and it also helps to remove some low-melting-point impurities. If the temperature is lower than 1200°C, it may not be possible to ensure that all electrolytic copper plates are completely melted, and the unmelted part may remain at the bottom of the crucible, which not only wastes raw materials, but also may cause inclusions and other problems in subsequent processing. On the contrary, if the temperature is higher than 1300°C, the chemical reaction between the copper liquid and the surrounding environment, especially the oxidation reaction, will be significantly aggravated. Even if a protective covering layer and an inert gas are used, this risk cannot be completely eliminated, which will lead to the formation of more oxides, thereby reducing the purity of the copper liquid.
[0067] In the above embodiment, the temperature of the launder is set between 1200°C and 1300°C because: the melting point of copper is about 1085°C, but in actual operation, considering the heat loss and in order to ensure that the copper liquid does not solidify or become too viscous in the launder, the launder temperature needs to be set higher. The temperature range of 1200°C to 1300°C can ensure that the copper liquid has good fluidity, so that it can flow into the crystallizer smoothly. In addition, although a variety of measures (such as covering flake graphite, nano carbon tubes or passing argon) are taken during the smelting process to prevent the copper liquid from oxidizing, there is still a risk of being exposed to oxidation in the air when the copper liquid passes through the launder. By setting the temperature of the launder within this range, it helps to reduce the possibility of copper liquid being oxidized, because although the speed of the oxidation reaction is accelerated at high temperature, it can also better play the role of protective gas (such as argon), making the oxide easier to float and be removed. It should be noted that if the temperature of the launder is too low (less than 1200°C), the copper liquid in the launder may become too viscous, poor in fluidity, and may even begin to solidify in the launder, thus affecting subsequent processing. If the temperature of the launder is too high (greater than 1200°C), even with appropriate protective measures, the excessively high temperature will intensify the oxidation reaction of the copper liquid, thus affecting the purity of the copper liquid.
[0068] In the above embodiments, the present application further improves the preparation process, that is, before the copper ingot is sawed, a cold treatment operation is added to the copper ingot, which specifically includes the following steps:
[0069] Step 1: Move the copper ingot into the pre-cooling zone of the liquid nitrogen cryogenic treatment box, and quickly cool the surface of the copper ingot to about -80°C by circulating cold air or liquid nitrogen spray. This rapid cooling process is intended to form a harder surface layer that can protect the internal structure from thermal shock during the subsequent cryogenic treatment process.
[0070] Step 2: Close the pre-cooling zone, open the door of the main cooling chamber, and send the copper ingot into the main cooling chamber. At this stage, the temperature is further reduced to minus 196°C (liquid nitrogen boiling point) by direct injection of liquid nitrogen. The copper ingot is kept at this extremely low temperature for a certain period of time (for example, 30 minutes to 2 hours) so that the residual stress in the entire ingot body is fully released. In addition, cryogenic treatment can also promote the transformation of certain metastable phases into more stable crystal structures, thereby optimizing the mechanical properties of the material.
[0071] Step 3: After cryogenic treatment, gradually turn off the liquid nitrogen supply, start the heating system, and use graded heating to slowly heat the copper ingot back to room temperature. The temperature rise at each stage does not exceed 20°C, and stays at each temperature point for a long enough time (such as 0.5h) to ensure that the heat can be evenly diffused to avoid new thermal stress.
[0072] In summary, before sawing, the residual thermal stress inside the copper ingot can be fully released by cold treating the copper ingot, compared with not cold treating it. In addition, certain internal stresses will inevitably be generated during the casting and cooling process, and if these stresses are not eliminated, the copper ingot may cause deformation, cracking and other problems during subsequent processing or use. However, through deep cryogenic treatment, these internal stresses can be effectively reduced, thereby improving the dimensional stability and mechanical properties of the copper ingot. Furthermore, after cold treatment, a harder surface layer will be formed on the surface of the copper ingot, which can provide better support during the sawing process and reduce the vibration and deviation generated during sawing. At the same time, since cold treatment reduces internal stress, crack propagation is not easy to occur during the sawing process, thereby improving the quality and accuracy of sawing and extending the service life of the saw blade.
[0073] Next, the present application tested the various elements in the oxygen-free copper ingot prepared by the above embodiment, and the test results are shown in Table 1:
[0074] Table 1
[0075]
[0076] In Table 1, the copper content obtained based on each embodiment is 99.9962%, 99.9964%, and 99.9966%, respectively, all exceeding the 4N standard (99.99%), and even close to the 5N (99.999%) standard, which is greatly improved compared to the copper content of existing oxygen-free copper (99.95-99.98%). In addition, it can be seen from Table 1 that the oxygen content in the high-purity oxygen-free copper ingot prepared by the present application is extremely low, for example, 0.0002% in Example 1, 0.0003% in Example 2, and 0.00025% in Example 3, which is far below the standard of 5ppm. In addition, other impurity elements such as lead (Pb), zinc (Zn), iron (Fe), etc. are also kept at very low levels, which helps to reduce the occurrence of hydrogen embrittlement and other defects.
[0077] Figure 2 This is a macroscopic metallographic diagram of an oxygen-free copper ingot prepared by the method described in this application. Figure 3 This is a microscopic metallographic diagram of an oxygen-free copper ingot prepared by the method described in this application. Figure 4 This is a macroscopic metallographic diagram of the existing oxygen-free copper ingot.
[0078] from Figure 2 It can be seen that the oxygen-free copper ingot prepared by the method described in the present application has a very uniform and fine grain structure. The surface of the ingot is smooth, without obvious cracks, pores or other defects, which reflects that the present application avoids damage caused by impurities or thermal stress through precise control of various parameters during the smelting and casting process. Figure 3It can be seen that the oxygen-free copper ingot prepared by the method described in the present application shows higher grain uniformity, and almost no surface defects are observed, indicating that internal stress and external contamination are effectively reduced during the preparation process.
[0079] Figure 4 In the figure, it shows a large grain difference, with some areas of larger grains and others of smaller grains, as well as some surface defects such as cracks, pores or oxidation marks. In particular, the color change on the surface of the ingot can be seen in the figure, which indicates that it contains high impurities or has undergone local oxidation.
[0080] In summary, through Figures 2 to 4 The comparison can further demonstrate the advancement of the preparation method described in the present application. The oxygen-free copper ingot prepared by this method shows significant advantages both at the macro and micro levels.
[0081] In another exemplary embodiment, the present application also provides a radio frequency component, which is prepared from high-purity oxygen-free copper, and the high-purity oxygen-free copper is prepared by any of the preparation methods described above, wherein the radio frequency component includes an antenna, a filter, a coupler, and the like.
[0082] In this embodiment, since the high-purity oxygen-free copper ingots prepared based on the embodiments described in this application have extremely high electrical conductivity and extremely low resistivity, good results can be achieved when they are applied to radio frequency components such as antennas, filters, and couplers. For example, applying high-purity oxygen-free copper ingots to antennas can ensure the high efficiency of antenna signal transmission and reception, reduce attenuation, and improve communication quality and coverage. When applied to filters, it helps to achieve narrow bandwidth, low insertion loss, and high Q value, thereby improving frequency selectivity and overall performance. Couplers require materials to have good conductivity and thermal stability. High-purity oxygen-free copper can meet these harsh conditions and ensure the accuracy and stability of coupler signal transmission.
[0083] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a high-purity oxygen-free copper ingot, characterized in that: The preparation method comprises: Preheating and drying the electrolytic copper plate; Smelting the dried electrolytic copper plate to obtain copper liquid; The copper liquid is kept warm and stirred during the keeping warm process to purify the copper liquid; The purified copper liquid is initially cooled to obtain a copper ingot; The copper ingot is drawn, the copper ingot is secondary cooled during the drawing process, and the secondary cooled copper ingot is sawed and cast to obtain a high-purity oxygen-free copper ingot.
2. The preparation method according to claim 1, characterized in that: The electrolytic copper plate is preheated in a step-by-step heating manner, with the preheating temperature being 300° C. to 500° C.
3. The preparation method according to claim 1, characterized in that: The melting temperature of the electrolytic copper plate is 1200°C to 1300°C.
4. The preparation method according to claim 1, characterized in that: After obtaining the copper liquid, it is necessary to cover the surface of the copper liquid with flake graphite, and the thickness of the flake graphite is 50 mm to 100 mm.
5. The preparation method according to claim 1, characterized in that: The insulation time of the copper liquid is 1h to 4h.
6. The preparation method according to claim 1, characterized in that: The purified copper liquid is cooled by cooling water for primary and secondary cooling. The flow rate of cooling water for primary cooling is set to 40m 3 / h~50m 3 / h.
7. The preparation method according to claim 6, characterized in that: The cooling water adopts a flow path from top to bottom.
8. The preparation method according to claim 7, characterized in that: During the secondary cooling of the copper ingot, the spray intensity of the cooling water is set in a gradient manner.
9. The preparation method according to claim 1, characterized in that: Before sawing and casting the copper ingot after secondary cooling, the copper ingot needs to be cold treated.
10. A radio frequency component, characterized in that: The radio frequency component is made of high-purity oxygen-free copper, and the high-purity oxygen-free copper is obtained by the preparation method according to any one of claims 1 to 9.